Strukturasi Ajaran Tattwa Dalam Teks Tattwa Jnana - Hari Harsananda (Kamaya: Jurnal Ilmu Agama, 2021)
Tattwa is a concept that becomes the foundation for the religious system of the Hindu community in Indonesia in general, and for the Hindu community in Bali in particular. The concept of tattwa is specifically contained in several types of lontar texts such as Whraspati tattwa, Ganapati Tattwa, Bhuwana Kosa to Tattwa Jnana. The tattwa teachings in the Tattwa Jnana text are structurally very clear Tattwa teachings, which contain the Cetana teachings which consist of the Tri Purusa concept, namely, Paramasiwa, Sada Siwa and Atmika tattwa as well as the Acetana teachings which are part of virtual cetana. In this tattwa jnana text, it also contains the process of emanation or the flow of the true soul or Paramasiva to become individual souls on this earth. There are also concepts about Triguna, triantah karana, Dasendriya, as well as Panca Tan Matra and Panca Maha Bhuta. The teaching of Yoga is also contained in this text as a means that can be done in an effort to achieve unity with Paramasiwa or known as the Moksa concept.